Introduction to cultural mathematics with case studies in the Otomies and the Incas - Gilsdorf, Thomas E. (Wiley, 2012)
"The topic of cultural mathematics (also called ethnomathematics) is a fascinating topic about the human aspects of mathematics, and it is easy to ask readers to participate in the topic by thinking about mathematics from their own perspectives. This book has two main parts, and Part I consists of several chapters that describe the major concepts of cultural mathematics. The topics include: cultural aspects of mathematics, numeration and number symbols, kinship relations, art and decoration, games and divination, and calendars. Part II includes two chapters consisting of case studies. The cultures studied are the Otomies of central Mexico and the Incas of South America. In these chapters, the concepts from Part I are applied to the particular culture, in order to put all the concepts together in one context. Each chapter concludes with exercises, followed by further notes about the topics discussed in that chapter. Hints and comments about the exercises are also provided at the end of the book. This book is roughly at the level of a reader who has taken college algebra; however, the most important prerequisite is an interest in the connections between mathematics and culture"--